On 3D symmetrical thermoelastic anticrack problems (Archives of Mechanics - Test, 2016)
A potential theory method is developed to solve a symmetrical thermoelastic problem of a cooling temperature field applied over the faces of a rigid sheet-like inclusion (an anticrack) in an elastic space. The governing boundary two-dimensional (2D) singular integral equations for an arbitrarily shaped anticrack are derived in terms of unknown thermal shear stress jumps. As an illustration, a complete solution expressed in elementary functions to the problemof a circular rigid inclusion subjected to a uniform temperature is presented and interpreted from the point of view of fracture theory.